2011
DOI: 10.1007/s11136-011-9875-x
|View full text |Cite
|
Sign up to set email alerts
|

Associations between objectively assessed physical activity levels and fitness and self-reported health-related quality of life in community-dwelling older adults

Abstract: Objectively assessed PA and physical fitness measures were positively associated with physical health HRQoL subscales as reported by community-dwelling older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
70
2
9

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(96 citation statements)
references
References 28 publications
15
70
2
9
Order By: Relevance
“…These results are consistent with another study where the BMI of older adults significantly declines that after 8 weeks of Thai dance on nine channels table (37). The results from body composition in our study showed that older subjects were able to achieve a decrease in BMI after 8 weeks of training (5 times/day), enhance at the same time their strength, balance and cardiorespiratory fitness, underlining the importance for older people to participate in regular training for their health, functionality and quality of life (38). However, in the present study, NME did not have a significant effect on systolic and diastolic blood pressure.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…These results are consistent with another study where the BMI of older adults significantly declines that after 8 weeks of Thai dance on nine channels table (37). The results from body composition in our study showed that older subjects were able to achieve a decrease in BMI after 8 weeks of training (5 times/day), enhance at the same time their strength, balance and cardiorespiratory fitness, underlining the importance for older people to participate in regular training for their health, functionality and quality of life (38). However, in the present study, NME did not have a significant effect on systolic and diastolic blood pressure.…”
supporting
confidence: 58%
“…American college of sports medicine recommended aerobic exercise training of sufficient intensity (≥ 60% of pre-training VO 2max ), frequency, and length (≥ 3 d-wk -1 for ≥ 16 wk) in order to VO 2max (8). Taking into account our NME program, specifically its short duration and intensity, we believe that the success of its performance is also dependent on peripheral adaptation, particularly the power and muscular strength of the lower limbs (38). Thus, the significant improvements in aerobic fitness can be, once more, attributed to increases muscular endurance resulting from the NME program training.…”
mentioning
confidence: 99%
“…This is consistent with results from other longitudinal studies focusing on specific population subgroups [18,20,32], but was for the first time unveiled using a nationally representative sample.…”
Section: Resultssupporting
confidence: 91%
“…The study of relation between strength and quality of life is scarce 8,10 , and in the present study no significant correlations were observed. It is known, for instance, that studies that investigated untrained older person showed better performance in the PHIS test it is associated with superior scores of quality of life in two domains of SF-36, the physique function (OR = 2.37) and vitality (OR = 1.83) 10 .…”
Section: Discussioncontrasting
confidence: 76%
“…Although muscle strength is a physical capacity fundamental to obtain success in the modality 3 , ghters did not show high values when compared with no ghters in the peak of handgrip isometric strength (PHIS), but the ghters showed lower fatigue rate when there is sustenance of contraction for 10 seconds 7 . Furthermore, it is well know that the PHIS have a positive correlation with health parameters [8][9][10] . Among institutionalized elderly, for instance, it was observed that lower levels of PHIS become the elderly susceptible to falls 11 .…”
mentioning
confidence: 99%